Empowering Muslim Rural Women through Digital Infrastructure and Zakat Community Development in Kahayya, Bulukumba - Haris, Basmawati; Fajrul, Muh (Institut Agama Islam Negeri (IAIN) Manado, 2025)
The empowerment of rural Muslim women represents a strategic issue in sustainable development in Eastern Indonesia, yet studies that simultaneously integrate digital infrastructure transformation with the role of Islamic philanthropy remain extremely limited. This study aims to analyse changes in the socio-economic roles of Muslim women in Kahayya Village, Kindang District, Bulukumba Regency, South Sulawesi, Indonesia, in the context of the introduction of basic infrastructure comprising roads, electricity, and internet access, as well as the presence of BAZNAS's Zakat Community Development (ZCD) programme as a community-based Islamic philanthropic instrument. This study employs a qualitative case study design. Data were collected through in-depth interviews with 15 informants, participatory observation across six field visits, and document review of BAZNAS ZCD programme reports. Analysis was conducted thematically using the Gender and Development (GAD) framework brought into dialogue with the maqasid al-shariah perspective. The findings reveal that infrastructure transformation significantly drives a shift in women's roles from the domestic sphere toward productive economic participation, improved access to education, and broader social engagement. The BAZNAS ZCD programme demonstrably strengthens this empowerment process through Islamic value-based entrepreneurship mentoring, which not only increases mustahiq income but also reinforces women's position in decision-making at the family and community levels. This study concludes that the synergy between digital infrastructure development and Islamic philanthropy constitutes a contextually grounded and sustainable empowerment model for rural Muslim women in Eastern Indonesia, provided it is supported by strengthened digital literacy and adequate cross-sectoral coordination.